Submarine canyon and fan systems of the California Continental Borderland - Normark, William R.; Piper, David J. W.; Romans, Brian W.; Covault, Jacob A.; Dartnell, Peter; Sliter, Ray W. (Geological Society of America Special Papers, 2009)
Late Quaternary turbidite and related gravity-flow deposits have accumulated in basins of the California Borderland under a variety of conditions of sediment supply and sea-level stand. The northern basins (Santa Barbara, Santa Monica, and San Pedro) are closed and thus trap virtually all sediment supplied through submarine canyons and smaller gulley systems along the basin margins. The southern basins (Gulf of Santa Catalina and San Diego Trough) are open, and, under some conditions, turbidity currents flow from one basin to another. Seismic-reflection profiles at a variety of resolutions are used to determine the distribution of late Quaternary turbidites. Patterns of turbidite-dominated deposition during lowstand conditions of oxygen isotope stages 2 and 6 are similar within each of the basins. Chronology is provided by radiocarbon dating of sediment from two Ocean Drilling Program sites, the Mohole test-drill site, and large numbers of piston cores. High-resolution, seismic-stratigraphic frameworks developed for Santa Monica Basin and the open southern basins show rapid lateral shifts in sediment accumulation on scales that range from individual lobe elements to entire fan complexes. More than half of the submarine fans in the Borderland remain active at any given position of relative sea level. Where the continental shelf is narrow, canyons are able to cut headward during sea-level transgression and maintain sediment supply to the basins from rivers and longshore currents during highstands. Rivers with high bedload discharge transfer sediment to submarine fans during both highstand and lowstand conditions.
id: 878; 10.1130/2009.2454(2.7)